Farmers’ choice of wetland agriculture: checking wetland loss and degradation in Lagos State, Nigeria (2013)
The issue of food security has received increasing emphasis in developing countries, particularly in the cities. The emphasis on food security has engendered agricultural expansion and encroachment on the coastal and inland wetlands in these nations. To facilitate and sustain the security of food in the developing countries local and international policies have been designed and employed; they have specifically targeted abounding food production towards ensuring human survival in the cities. However, the various ecological and socio-economic benefits derivable from the preservation of wetlands and inland valleys in these urban environments may be lost, with the transformation in the land use and cover. This study is therefore concerned with how wetland degradation and loss can be checked and mitigated, focusing on the developing countries and their cities. In this respect, the farmer’s awareness of the impacts of wetland cultivation and the role of accessibility, socio-economic and biophysical factors influencing the choice of wetland farming are examined. To this end, structured questionnaire on choice of wetland agriculture in the urban and periurban wetland areas of Lagos city was administered to the farmers. Simple frequency analysis is used to explain and interpret the data generated. The data reveals a generally low level of farmers’ awareness of the implication of wetland cultivation; it shows different categories of factors influencing the choice of wetland farming. Provision of irrigation infrastructure and improvement in living standard of the people through poverty eradication can discourage disadvantageous encroachment on wetlands in cities.